Integrated approach for noncommunicable disease management in the Americas - Silvana Luciani; Irene Agurto; Reynaldo Holder; Roberta Caixeta; Anselm JM Hennis (Pan American Health Organization, 2022)
An overview of an integrated approach to improve noncommunicable disease (NCD) management is presented, along with tools on integrating NCD management as part of health system strengthening in the Americas. The study is based on an analysis of Pan American Health Organization/World Health Organization (PAHO/WHO) data and publicly available information on NCD care and capacity, disruptions in NCD services, and guidance on NCD management. Gaps in NCD care are highlighted, in which an estimated 43.0% of men and 28.0% of women with hypertension in Latin America remain undiagnosed; and for those with diabetes, 32.8% in Central and South America are undiagnosed. Yet, only 17/35 countries (49%) in the Americas report having evidence-based national guidelines for NCD management through a primary care approach and only 7/35 countries (20%) report provision of drug therapy, including glycaemic control for eligible persons. To improve NCD management, an integrated approach is needed to coordinate and deliver care across the levels of the health system. This includes increasing primary care capacity and competencies to address multiple chronic conditions, and integration with other complementary programs to avoid missing opportunities for NCD diagnosis and management. An integrated approach to NCD management, and implementation of available tools, should be part of rebuilding health systems after the COVID-19 pandemic.